Reactions to Crime Project, 1977 (Chicago, Philadelphia, San Francisco): Survey on Fear of Crime and Citizen Behavior ([Verlag nicht ermittelbar], 1984)
This survey was conducted by the Center for Urban Affairs and Policy Research at Northwestern University to gather information for two projects that analyzed the impact of crime on the lives of city dwellers. These projects were the Reactions to Crime (RTC) Project, which was supported by the United States Department of Justice's National Institute of Justice as part of its Research Agreements Program, and the Rape Project, supported by the National Center for the Prevention and Control of Rape, a subdivision of the National Institute of Mental Health. Both investigations were concerned with individual behavior and collective reactions to crime. The Rape Project was specifically concerned with sexual assault and its consequences for the lives of women. The three cities selected for study were Chicago, Philadelphia, and San Francisco. A total of ten neighborhoods were chosen from these cities along a number of dimensions -- ethnicity, class, crime, and levels of organizational activity. In addition, a small city-wide sample was drawn from each city. Reactions to crime topics covered how individuals band together to deal with crime problems, individual responses to crime such as property marking or the installation of locks and bars, and the impact of fear of crime on day-to-day behavior -- for example, shopping and recreational patterns. Respondents were asked several questions that called for self-reports of behavior, including events and conditions in their home areas, their relationship to their neighbors, who they knew and visited around their homes, and what they watched on TV and read in the newspapers. Also included were a number of questions measuring respondents' perceptions of the extent of crime in their communities, whether they knew someone who had been a victim, and what they had done to reduce their own chances of being victimized. Questions on sexual assault/rape included whether the respondent thought this was a neighborhood problem, if the number of rapes in the neighborhood were increasing or decreasing, how many women they thought had been sexually assaulted or raped in the neighborhood in the previous year, and how they felt about various rape prevention measures, such as increasing home security, women not going out alone at night, women dressing more modestly, learning self-defense techniques, carrying weapons, increasing men's respect of women, and newspapers publishing the names of known rapists. Female respondents were asked whether they thought it likely that they would be sexually assaulted in the next year, how much they feared sexual assault when going out alone after dark in the neighborhood, whether they knew a sexual assault victim, whether they had reported any sexual assaults to police, and where and when sexual assaults took place that they were aware of. Demographic information collected on respondents includes age, race, ethnicity, education, occupation, income, and whether the respondent owned or rented their home.